Right versus left sided metastatic colorectal cancer: Teasing out clinicopathologic drivers of disparity in survival. Issue 3 (13th February 2019) - Mendis, Shehara; Beck, Sophie; Lee, Belinda; Lee, Margaret; Wong, Rachel; Kosmider, Suzanne; Shapiro, Jeremy; Yip, Desmond; Steel, Simone; Nott, Louise; Jennens, Ross; Lipton, Lara; et al.
Abstract: Background: Metastatic colorectal cancer (mCRC) patients with a right‐sided primary (RC) have an inferior survival to mCRC arising from a left‐sided primary (LC). Previous analyses have suggested multiple factors contribute. Methods: The Treatment of Recurrent and Advanced Colorectal Cancer (TRACC) Registry prospectively captured data on consecutive mCRC patients. RC were defined as tumors proximal to the splenic flexure; LC were those at and distal to the splenic flexure and included rectal cancers. Patient,  tumor, treatment, and survival data were analyzed stratified by side. Results: Of 2306 patients enrolled from July 2009–March 2018, 747 (32%) had an RC. Patients with RC were older, more likely to be female and have a Charlson score ≥3. RC were more frequently BRAF mutated, deficient in mismatch repair, associated with peritoneal metastases, and less likely to receive chemotherapy. Progression‐free survival on first‐line systemic therapy was inferior for RC patients (8.1 vs. 10.8 months, hazard ratio [HR] for progression in RC 1.38, P  < 0.001). Median overall survival for all RC patients was inferior (19.6 vs. 27.5 months, HR for death in RC 1.44, P  < 0.001), and inferior within the treated (21 vs. 29.5 months, HR 1.52, P  < 0.001) and untreated subgroups (5.9 vs. 10.3 months, HR 1.38, P  = 0.009). Primary side remained a significant factor for overall survival in multivariate analysis. Conclusion: Our data from a real‐world population confirms the poorer prognosis associated with RC. Primary tumor location remains significantly associated with overall survival even when adjusting for multiple factors, indicating the existence of further side‐based differences that are as yet undefined.